FLIPPED LEARNING APPROACH TO FOSTER BENINESE EFL ADVANCED STUDENTS’ ORAL COMMUNICATION CASE STUDY OF CEG VAKON - TEBA, Corneille Sourou (My University, 2024)
This paper investigates the flipped learning approach to foster Beninese EFL Advanced students’ oral communication. This research work also has as objective to solve some challenges faced by learners in flipping learning approach. To reach this goal, ten (10) EFL teachers and one hundred (100) beginners are sampled purposively in CEG Vakon. Firstly, to collect data some questionnaires have been addressed to the selected students to understand the difficulties they generally face to speak English. Classroom observations and interview have also been carried out. The second stage deals with the experimental process. It has involved forty (40) students randomly split into two groups of twenty (20): an experimental group received the treatment (Flipped Classroom to teaching) and a control group without treatment. Both groups have been submitted to a pre-test and posttest after a period. The results of the study show that most of the learners have difficulties in oral communication because their level in grammar is low and they lack vocabulary. This research shows that flipped learning can be of great use to foster EFL students’ oral communication performance.
Keywords: Keywords: Oral Communication; Flipped Learning; Skills; Performance